ANALYSIS OF THE RESULTS OF MODERN GEODETIC MONITORING OF EARTH DAMS OF SOME RESERVOIRS OF THE REPUBLIC OF ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
The results of research and analysis of data obtained by geodetic observations of reservoirs located in the Syunik Region on the Vorotan River, represented by the Spandaryan, Shamb and Tolors reservoirs and the Tatev daily regulating reservoir, are presented. Using geodetic technologies provides an opportunity to conduct a complete cartography of water systems and create a database. In the management process, it is impossible to respond rapidly without the help of a database and corresponding tools. As demonstrated by international experience, these technologies are mandatory in the management process of water systems. High-tech work can improve the accuracy of observations and measurements, as well as optimize expenses and time.
Keywords: dam; GNSS technologies; geodetic monitoring; cartography; drone; mining